Selection of soybean pods by the stink bugs, Nezara viridula and Piezodorus guildinii - Molina, Gonzalo Alberto Roman (2012)
Different biological parameters of the stink bugs, Nezara viridula L. and Piezodorus guildinii Westwood (Hemiptera: Pentatomidae), are affected by the developmental stage of the soybean (Glycine max Merrill) pods they feed on. These effects of the soybean on the stink bugs could represent a selection pressure leading to the ability of these species to discriminate the phenological stage of soybean pods, and, therefore, to exhibit feeding preferences. We designed three studies: (1) Distant detection of soybean pods through an olfactometer; (2) Free choice tests to evaluate preferences for soybean pods of different developmental stages; (3) No choice tests to study effects of soybean pod development on feeding time and number of probes. Stink bugs showed no differential response to olfactometer arms with or without soybean pods, suggesting an inability to detect soybean volatiles. Free choice tests showed no species effects on pods selection, but significant differences among fifth instar nymphs, adult male, and adult females. Fifth instar nymphs fed more frequently on soybean pods of advanced development stages compared to female adults, despite previous evidence showing poor development of stink bugs fed pods of the same stage. No choice tests showed significant effects of stink bug species, stink bug stage and sex, and soybean pod phenology. N. viridula expressed shorter feeding times and higher numbers of probes than P. guildinii. The highest numbers of probes of both species were observed when they were fed soybean pods in early phenological stages. When placed in direct contact with food, fifth instar nymphs prefered to feed on more developed pods, despite these pods being suboptimal food items. These results suggest that for the ecological time framework of soybean-stink bugs coexistence, around thirty-five years in Argentina, the selection pressure was not enough for stink bugs to evolve food preferences that match their performance on soybean pods of different development stages.